Effect of Rhizobium strains and different fertility levels on productivity, quality, nutrient content and uptake of blackgram (Vigna mungo L.) in Typic Haplustepts - Anju Kanwadiya,; S. L. Narolia,; Prakrati Malakar, (Annals of Agricultural Research, 2023)
A field experiment was conducted during Kharif season of 2017 at the Instructional Farm (Agronomy), Rajasthan College of Agriculture, Udaipur to study the “Effect of Rhizobium strains and different fertility levels on productivity and quality of blackgram (Vigna mungo L.)”. The soil of the experimental site was clay loam in texture slightly alkaline in reaction, medium in available nitrogen and phosphorus and high in potassium. The experiment was laid out in factorial randomized block design with three replications. The experiment comprised four Rhizobium strains (Commercial strain I, Commercial strain II, Indigenous strain I (Urd-7D) and Indigenous strain II (Urd-8P) and one control and four fertility levels (Control, 50% RDF, 75% RDF and 100% RDF) were applied to the blackgram var. PU-31. Results indicate that seed inoculation with Indigenous strains I significantly increased pods plant-1, seeds pod-1 as well as seed, straw, biological yield and protein content over both commercial strains as well as un-inoculated control. However, it was found statistically at par with Indigenous strain II. The effect of Rhizobium strains significantly influences the N, P and K content and uptake by seed and straw. Similarly, application of 100% RDF significantly increased pods plant-1, seeds pod-1, seed, straw, biological yield as well as protein content over other fertility levels. The application of 100% RDF also increased N, P and K content and uptake by seed and straw of blackgram over rest of fertility treatment.